Qualidade da água e fluxos de nutrientes na interface sedimento-água nas represas do Rio Tietê - Soares, Aluisio (Universidade Federal de São Carlos, 2003)
The first Law of Fick in one dimension was utilized for the calculation of those fluxes. In this work was calculated the concentrations of the following chemical species: nitrate, nitrite, ammonium, total nitrogen, orthophosphate, total phosphorus, dissolved organic carbon (DOC), cloride, fluoride, sulfate and silica reactive, as well as the biogeochemicals variables in situ: pH, redox potential , electric conductivity, temperature and dissolved oxigen. The Billings reservoir presented the highest fluxes from the sediment to the water column for nitrate, ammonium, chloride and sulfate: 178, 2181, 2945 and 5821 mg cm-2 year-1, respectively, denoting that this environment is suffering great contribution of these nutrients and consequently presents a larger fluxes for the water column. A study of seasonal variation in the water columm of Barra Bonita reservoir was also done for evaluate in the water column in the Barra Bonita reservoir for evaluate the behavior distribution of the chemical species during a complete hidrologic year. The data, for most of the studied variables indicated that during the drought period occurs a decreasing in concentrations, which can infer that those elements should have anthropogenic origin. The nitrate concentration, reaches a pick of 1,9 mg L-1 for the water column in the period of smaller pluviometer index, is one of the indicators of this tendency. Another data group was sampled for the same parameters and refer to the verification of the bedding stratification occurrence in the water column of Barra Bonita reservoir. The result demonstrated that these phenomenon does not happen for this reservoir because the variation in the concentration of the studied variables reflect only the dynamics of the reservoir for your handling, in addiction, there is not separation of masses of water in different horizontal layers caused by differences of temperatures and chemical water composition.
Keywords: Limnologia; Água - qualidade; Fluxos de nutrientes; Tietê, Rio (SP); CIENCIAS EXATAS E DA TERRA::QUIMICA